Thromboprophylaxis for trauma patients (2013)
ABSTRACT: BackgroundTrauma is a leading causes of death and disability in young people. Venous thromboembolism (VTE) is a principal cause of death. Traumapatients are at high risk of deep vein thrombosis (DVT). The incidence varies according to the method used to measure the DVT andthe location of the thrombosis. Due to prolonged rest and coagulation abnormalities, trauma patients are at increased risk of thrombusformation. Thromboprohylaxis, either mechanical or pharmacological, may decrease mortality and morbidity in trauma patients whosurvive beyond the first day in hospital, by decreasing the risk of VTE in this population.A previous systematic review did not find evidence of eJectiveness for either pharmacological or mechanical interventions. However,this systematic review was conducted 10 years ago and most of the included studies were of poor quality. Since then new trials havebeen conducted. Although current guidelines recommend the use of thromboprophylaxis in trauma patients, there has not been acomprehensive and updated systematic review since the one published.ObjectivesTo assess the eJects of thromboprophylaxis in trauma patients on mortality and incidence of deep vein thrombosis and pulmonaryembolism. To compare the eJects of diJerent thromboprophylaxis interventions and their eJects according to the type of trauma.Search methodsWe searched The Cochrane Injuries Group Specialised Register (searched April 30 2009), Cochrane Central Register of Controlled Trials2009, issue 2 (The Cochrane Library), MEDLINE (Ovid) 1950 to April (week 3) 2009, EMBASE (Ovid) 1980 to (week 17) April 2009, PubMed(searched 29 April 2009), ISI Web of Science: Science Citation Index Expanded (SCI-EXPANDED) (1970 to April 2009), ISI Web of Science:Conference Proceedings Citation Index-Science (CPCI-S) (1990 to April 2009).Selection criteriaRandomized controlled clinical trials involving people of any age with major trauma defined by one or more of the following criteria:physiological: penetrating or blunt trauma with more than two organs and unstable vital signs, anatomical: people with an Injury SeverityScore (ISS) higherthan 9, mechanism: people who are involved in a 'high energy' event with a risk for severe injury despite stable or normalvital signs. We excludeed trials that only recruited outpatients, trials that recruited people with hip fractures only, or people with acutespinal injuries.ed trials that only recruited outpatients, trials that recruited people with hip fractures only, or people with acutespinal injuries.